Exploring Young Learners’ Needs in Multimodal Text Design for Integrating Sustainable Education into ELT - Jasmine, Malihah Putri; Silvhiany, Sary; Inderawati, Rita (Universitas Pendidikan Mandalika, 2025)
This study investigates the integration of sustainable education into English Language Teaching (ELT) for fifth-grade students at SDN 115 Palembang. As sustainable development gains global urgency, education plays a crucial role in fostering environmental awareness among young learners. However, limited resources integrating climate change topics into ELT highlight a significant research gap. In this context, multimodal texts-combining text, visual, audio and interactive elements-are a solution as an effective and interesting learning media. This research focuses on conducting a needs analysis regarding the use of multimodal texts in climate change learning in ELT. A mixed-methods approach was employed, combining quantitative surveys with 30 students and qualitative interviews with English teacher and vice principal of curriculum. Data were analyzed using descriptive statistics for the quantitative data and thematic analysis for the qualitative data. Findings highlight the urgent need for multimodal texts to support sustainable education literacy in ELT. Students showed a strong interest in learning about climate change and taking action to protect their environment, emphasizing the effectiveness of multimodal texts in making these concepts more engaging and accessible. While students recognize the importance of learning English and climate change topics, existing ELT materials lack sufficient multimodal resources to facilitate this integration. It can be concluded that multimodal texts are urgently needed to support sustainable education literacy in ELT. Therefore, this study advocates for the integration of digital multimodal texts to enhance both language learning and sustainability education.